2017
DOI: 10.13189/sa.2017.050905
|View full text |Cite
|
Sign up to set email alerts
|

Training and Adolescent Adjustment among Academically Gifted European and Chinese American Students

Abstract: Training (jiao xun) has been proposed as an indigenous form of Chinese parenting. Does it exist in other populations? If so, how might it be associated with developmental outcomes? We examined the relationships of training to adolescent academic, psychological, and school adjustment in a sample of 214 Chinese American and 125 European American academically gifted students. We found that training also occurs in European American families with academically gifted children. There were other ethnic similarities: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
0
2
0
1
Order By: Relevance
“…Finally, while these parents wish for their children to meet markers of success including reproducing class and maintaining their faith-and support these definitions using school choice and organization of daily life-we do not yet know if their children will ultimately meet these benchmarks. A strict frame has caused many American-born Asians to feel like failures in the eyes of their parents, no matter how much education they attain or how much they earn in their current position (Chang and Qin 2017;Lee and Zhou 2015). What happens if third-generation Muslim Americans feel unsuccessful regardless of their faith, levels of religiosity, or character development?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, while these parents wish for their children to meet markers of success including reproducing class and maintaining their faith-and support these definitions using school choice and organization of daily life-we do not yet know if their children will ultimately meet these benchmarks. A strict frame has caused many American-born Asians to feel like failures in the eyes of their parents, no matter how much education they attain or how much they earn in their current position (Chang and Qin 2017;Lee and Zhou 2015). What happens if third-generation Muslim Americans feel unsuccessful regardless of their faith, levels of religiosity, or character development?…”
Section: Discussionmentioning
confidence: 99%
“…Since Lareau's study examined White and Black families, questions regarding how other minority groups reproduce socioeconomic status and enable upward mobility in their children's generation have proliferated. Scholars have found that the concerted cultivation type of parenting is common especially among Asian American parents, finding patterns of parents' strategic organization of their children's lives to produce favorable socioeconomic outcomes (Chang and Qin 2017;Chung 2016;Dhingra 2020;Lee and Zhou 2015;Tuan 1999). Lee and Zhou (2015) found that highly educated Asian immigrant parents define success for their American-born children as earning straight A's, graduating as the high school valedictorian, earning a degree from an elite university, attaining an advanced degree, and working in one of four high status professional fields: medicine, law, engineering, and science.…”
Section: Cultural Logics Of Parentingmentioning
confidence: 99%
“…Jadi, ketika para anak Cina-Amerika dalam sampel menjalani pelatihan pengasuhan anak, mereka mungkin merasakan konotasi positif di balik pengasuhan anak (misalnya, orang tua mengambil tanggung jawab mereka untuk mendisiplinkan mereka), sehingga pengasuhan anak ini memiliki implikasi positif untuk keterlibatan sekolah mereka (Chang & Qin, 2017).…”
Section: Pengasuhan Tiger Parentingunclassified